The Molecular Basis of Resilience: A Narrative Review - Ryan, Megan; Ryznar, Rebecca (Frontiers in Psychiatry, 2022)
Resilience refers to the adaptability of a person - an ability to “bounce-back” from stressors. We question if resilience can be targeted to increase a person’s resilience and decrease the risk of stress-related disorders. Unfortunately, the molecular origins of resilience are complicated and not yet well understood. In this review, we examine the various physiological biomarkers of resilience, including the associated genes, epigenetic changes, and protein biomarkers associated with resilient phenotypes. In addition to assessing biomarkers that may indicate higher levels of resilience, we also review at length the many biomarkers that confer lower levels of resilience and may lead to disorders of low resilience, such as anxiety and depression. This large and encompassing review may help to identify the possible therapeutic targets of resilience. Hopefully these studies will lead to a future where stress-related disorders can be prevented, rather than treated.